Incidental Detection of Radiotracer Uptake in Spindle Cell Lipoma on 18F-PSMA PET/CT. (27th October 2022) - Hod, Nir; Sherf, Yehonatan; Lantsberg, Sophie
Abstract: An 84-year-old man underwent 18 F–prostate-specific membrane antigen (PSMA) PET/CT for staging of a newly diagnosed prostate adenocarcinoma. PET/CT revealed high 18 F-PSMA uptake in a thigh mass, which was initially suspected for a metastasis. Histopathology revealed a rare entity of spindle cell lipoma, which should be added to the reported list of neoplasms that can show "false-positive" PSMA uptake during evaluation of patients with prostate carcinoma representing a potential interpretative pitfall.